Humanizing Science: A Narrative Inquiry into the Integration of Historical Context in STEM Education - Samsinas Samsinas; Clara Mendes; Rafaela Lima (Yayasan Adra Karima Hubbi, 2026)
Background. The integration of historical context in STEM education has gained increasing attention as a means to enhance student engagement and comprehension. STEM fields, traditionally perceived as highly technical, often lack connections to real-world applications and human stories. By incorporating historical narratives into STEM curricula, educators can humanize the subject matter and make scientific concepts more relatable. Purpose. This study explores the role of historical context in STEM education through a narrative inquiry approach. The research aims to investigate how educators incorporate history into their teaching practices and the impact this integration has on students’ learning experiences. Method. A qualitative approach was employed, utilizing interviews and reflective journals from STEM educators and students. Results. The findings reveal that incorporating historical context significantly enhances student engagement, fosters a deeper understanding of scientific concepts, and increases the relevance of STEM subjects in students' lives. The study also highlights the challenges educators face in integrating history into their teaching, particularly in terms of curriculum constraints and the lack of resources. Conclusion. The research concludes that historical context is a valuable tool in humanizing STEM education, making it more engaging and accessible. This approach promotes a more holistic understanding of science, emphasizing its societal relevance and the human dimensions behind scientific discoveries.